Do real interest rates converge? Evidence from the European Union - Michael G. Arghyrou; Andros Gregoriou; Alexandros Kontonikas (Cardiff University, Cardiff Business School, 2007)
We test for real interest rate convergence in the EU25 area. Our contribution is twofold: first, we account for the previously overlooked effects of structural breaks on real interest rate differentials. Second, we test for convergence against the EMU average. For the majority of our sample countries we obtain evidence of convergence towards the latter. This, however, is a gradual process subject to structural breaks, typically falling close to the launch of the euro. Our ?ndings have important implications relating to the single monetary policy and the progress new EU members have achieved towards joining the euro.
Keywords: F21; F32; C15; C22; 330; Real interest rates; Convergence Structural breaks; EU; EMU; Wirtschaftsintegration; Realzins; Währungsunion; Euro; EU-Staaten